Systemic treatment of patients with locally advanced or metastatic cholangiocarcinoma – an Austrian expert consensus statement - Taghizadeh, Hossein; Djanani, Angela; Eisterer, Wolfgang; Gerger, Armin; Gruenberger, Birgit; Gruenberger, Thomas; Rumpold, Holger; Weiss, Lukas; Winder, Thomas; Wöll, Ewald; Prager, Gerald W. (Frontiers in Oncology, 2023)
Locally advanced or metastatic cholangiocarcinoma is an aggressive carcinoma with a dismal prognosis. For the first-line treatment of locally advanced or metastatic cholangiocarcinoma, cisplatin/gemcitabine has been the standard of care for more than 10 years. Its combination with the immune checkpoint inhibitor durvalumab resulted in an efficiency improvement in the phase III setting. Regarding the use of chemotherapy in the second line, positive phase III data could only be generated for FOLFOX. The evidence base for nanoliposomal irinotecan (Nal-IRI) plus 5-fluorouracil (5-FU) and leucovorin (LV) is contradictory. After the failure of first-line treatment, targeted therapies can be offered if the molecular targets microsatellite instability-high (MSI-H), IDH1, FGFR2, BRAF V600E, and NTRK are detected. These targeted agents are generally preferable to second-line chemotherapy. Broad molecular testing should be performed, preferably from tumor tissue, at the initiation of firstline therapy to timely identify potential molecular targets.